Pensamiento lateral, creatividad y emprendimiento - Henry de Jesús Gallardo-Pérez; Mawency Vergel-Ortega; César Augusto Dávila Carrillo (Mundo Fesc)
Lateral thinking is closely related to creative thinking and is open to anyone interested in new ideas. Objective: To establish the relationship between problem-based learning as a pedagogical intervention to identify entrepreneurial action proposals in order to develop lateral thinking in first-semester students in academic university business programs and to establish its relationship with the development of their creativity. Method: A multi-method approach that combines qualitative research using ethnographic method with quantitative research through factor analysis with a quasi-experimental field design. Results: Collaborative learning as a result of fieldwork in solving environmental problems develops creativity and the ability to propose entrepreneurial ideas. Students in the first semesters of business programs show a favorable disposition to develop their creativity.